The Role of The Business World Industry Through a Teaching Practice Program in Increasing the Competence of Vocational School Graduates - Arsyad, Junaidah; Ambiyar, Ambiyar; Jalinus, Nizwardi; Fadhilah, Fadhilah; Abdullah, Rijal (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
The current increase in the number of unemployed is one of the impacts of the low qualifications of graduates so that they are not absorbed in the job market and this is a very serious problem and requires special handling and strategies to be overcome. SMK as an educational institution that produces a skilled workforce still leaves a number of problems related to skills that link and match with the world of work. It is hoped that the role of practitioners in the industrial world will be an alternative solution to this problem. This research is a type of research and development or Research and Development (R&D). The research is a qualitative research with data collection techniques in this study carried out through library survey activities, observation by observing the learning process, distributing questionnaires and documenting activities. Based on the results of the research, it was concluded that the role of world practitioners from the world of work is very effective and can be an alternative in solving competency problems for graduates from the Vocational High School level. Keywords: Practitioners, Competence, Graduates,